Web 2.0 Technologies in Journalism: Are Web 3.0 and Journalism 3.0 in sight? - Bago, Petra; Boras, Damir; Kišiček, Sanja (2010)
An ongoing issue is defining the concept of Web 2.0, starting with contrary stands of two acknowledged authorities when it comes to the World Wide Web: Sir Tim Berners-Lee and Tim O’Reilly. Putting theory aside, the technical aspect does not separate the World Wide Web analysts as much. The goal of this presentation is to give an overview of Web 2.0 technologies that have an impact on journalism, with introduction to the emerging concept of Web 3.0.
Projekt MZOS
ENG